2021
DOI: 10.1177/0976399620974202
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on FDIs, Remittances and Foreign Aids: A Case Study of Nepal

Abstract: The global economy has been severely paralysed, owing to the unprecedented crisis triggered by the COVID-19 pandemic, and different studies have indicated that the crisis is relatively more maleficent to the lower-income and middle-income economies. Methodologically, this study relied on the review and analysis of the grey literature, media reporting and data published by the Asian Development Bank, United Nations Conference on Trade and Development (UNCTAD), United Nations (UN), World Bank, International Mone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…Involvement is also seen as a key component in determining whether to buy fashion goods, and it has a significant impact on impulse purchases. Similarly, Kim et al (2002) and Bhattarai and Subedi (2021) demonstrated how engagement is a crucial element in fashion impulse purchases that influences either favourably or negatively depending on connected characteristics like impulse propensity, fun and enjoyment. According to Dhurup (2014), fashion participation is intimately linked to purchasing emotions and aspirations, with emotions serving as major indicators of impulsive purchases.…”
Section: Hypotheses Development Fashion Involvement Positive Emotions Impulse Buyingmentioning
confidence: 96%
“…Involvement is also seen as a key component in determining whether to buy fashion goods, and it has a significant impact on impulse purchases. Similarly, Kim et al (2002) and Bhattarai and Subedi (2021) demonstrated how engagement is a crucial element in fashion impulse purchases that influences either favourably or negatively depending on connected characteristics like impulse propensity, fun and enjoyment. According to Dhurup (2014), fashion participation is intimately linked to purchasing emotions and aspirations, with emotions serving as major indicators of impulsive purchases.…”
Section: Hypotheses Development Fashion Involvement Positive Emotions Impulse Buyingmentioning
confidence: 96%
“…A high reliance on remittances may produce a high risk to the country’s economy in any kind of international labour market crisis. Empirical studies demonstrating a significant drop in the remittance influx and reduction in the share of remittances in the gross national domestic product in earlier crises (for example, global financial crisis, Maoist insurgency in Nepal) are available (Sapkota, 2013 ), and for the recent Coronavirus (COVID-19) crisis, studies are emerging (Adhikari et al, 2022 ; Bhattarai & Subedi, 2021 ).…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…Remittances to GDP ratio of Nepal was only 2% in 2000, and it has risen sharply in the past 17 years. Remittances have a positive impact on the government revenue, helping to raise liquidity in the financial institutions of Nepal (Bhattarai & Subedi, 2021). Similarly, in the case of Kyrgyz Republic, remittances amounted to 31% of its GDP in 2016.…”
Section: A Glimpse Into the Inflows Of Remittances In The 17 Selected...mentioning
confidence: 99%